RETRACTED: Nogo-C Inhibits Peripheral Nerve Regeneration by Regulating Schwann Cell Apoptosis and Dedifferentiation - Jia, Bo; Huang, Wei; Wang, Yu; Zhang, Peng; Wang, Zhiwei; Zheng, Ming; Wang, Tianbing (Frontiers in Neuroscience, 2021)
Background: While Nogo protein demonstrably inhibits nerve regeneration in the central nervous system (CNS), its effect on Schwann cells in peripheral nerve repair and regeneration following sciatic nerve injury remains unknown. Methods: The post-injury expression of Nogo-C was assessed in an experimental mouse model of sciatic nerve-crush injury. A Nogo-C knockout (Nogo-C-/-) mouse was generated to observe the effect of Nogo-C on sciatic nerve regeneration, Schwann cell apoptosis, and myelin disintegration after nerve injury. Nogo-C was overexpressed in rat Schwann cells by adenovirus-mediated gene transfer, and the effects of Nogo-C on apoptosis and dedifferentiation of Schwann cells were observed in vitro. Results: The expression of Nogo-C protein at the distal end of the injured sciatic nerve increased from days 7 to 28 in wild type (WT) mice. Compared with the injured WT mice, the proportion of neuronal apoptosis was significantly diminished and the myelin clearance rate was significantly elevated in injured Nogo-C-/- mice on Day 7; the number of nerve fibers regenerated and the degree of myelination were significantly elevated in Nogo-C-/- mice on Day 14 after injury. In addition, the recovery of motor function was significantly accelerated in the injured Nogo-C-/- mice. The overexpression of Nogo-C in primary Schwann cells using adenovirus-mediated gene transfer promoted Schwann cells apoptosis. Nogo-C significantly reduced the ratio of c-Jun/krox-20 expression, indicating its inhibition of Schwann cell dedifferentiation. Conclusion: The expression of Nogo-C increases following peripheral nerve injury to promote Schwann cell apoptosis and inhibit Schwann cell dedifferentiation, thereby inhibiting peripheral nerve regeneration.